2016
DOI: 10.1002/chem.201603402
|View full text |Cite
|
Sign up to set email alerts
|

Trace Determination and Pressure Estimation of Fluorine F2 Caused by Irradiation Damage in Minerals and Synthetic Fluorides

Abstract: Irradiated alkali and earth alkali halides can form metal colloids and halogen molecules, which stay trapped inside the crystal. In this paper we provide F NMR spectroscopic evidence of trapped F fluids in heavy ion-bombarded synthesized LiF crystals as well as in a variety of the mineral Villiaumite (NaF). This is the 2nd mineral in which F is unambiguously detected in nature. The trace quantification of the latter is in the order of magnitude of 10 mol g . Pressures and densities of the F fluids are estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…The longitudinal relaxation time T 1 of the dissolved F 2 was determined by an inversion recovery experiment to be T 1 =13.5 ms (Figure S1.13 in the Supporting Information). This is approximately 300 times larger than T 1 for gaseous fluorine of 0.045 ms in the pressure range from 1 to 2 bar . This indicates that the fast relaxation owing to the spin‐rotation mechanism observed for gaseous fluorine is hindered and proves that the fluorine is indeed dissolved in peroxide 2 b .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The longitudinal relaxation time T 1 of the dissolved F 2 was determined by an inversion recovery experiment to be T 1 =13.5 ms (Figure S1.13 in the Supporting Information). This is approximately 300 times larger than T 1 for gaseous fluorine of 0.045 ms in the pressure range from 1 to 2 bar . This indicates that the fast relaxation owing to the spin‐rotation mechanism observed for gaseous fluorine is hindered and proves that the fluorine is indeed dissolved in peroxide 2 b .…”
Section: Resultsmentioning
confidence: 93%
“…This is approximately 300 times larger than T 1 for gaseous fluorine of 0.045 ms in the pressure range from 1t o2bar. [47] This indicates that the fast relaxation owing to the spin-rotation mechanism observed for gaseous fluorine is hindered and proves that the fluorine is indeed dissolved in peroxide 2b.…”
Section: Resultsmentioning
confidence: 99%
“…The goal is to monitor the intake of fluoride and maintain it at adequate levels so that optimal protection against dental caries is achieved, without excessive intake Štepec and Ponikvar-Svet: Fluoride in Human Health and Nutrition resulting in the appearance of adverse effects. Basic requirements for accurate and precise determination of fluorine in any type of the sample are: (1) the sample has to be appropriately pre-treated so that the required form can be determined; (2) interfering reactions or ions have to be effectively suppressed; (3) the final concentration of fluorine must be above the detection limit of the method; and (4) the result should be reported together with a measurement uncertainty (MU) evaluated in accordance Guide to the Expression of Uncertainty in Measurement (GUM).117. 117…”
Section: Fluorin(d)e Analytical Methodsmentioning
confidence: 99%
“…Finally, it is worth mentioning that in addition to these databases many studies reported the contents of total and/or free fluoride in different food items. [221][222][223][224][225][226][227] The results of these studies are difficult to compare, because the determined level of fluorine in food is among other influenced by: (1) the locality in which the food is grown; (2) the differences in the amount of fertilizer and pesticides applied or differences in feeding routine; (3) the type of processing the food receives; (4) the amount of water and the fluoride content of water used in their preparation; (5) different sample pre-treatment procedures; and (6) the differences in the analytical procedures. In addition, the re-…”
Section: Foodsmentioning
confidence: 99%
See 1 more Smart Citation